Assessment of Serum Dynamic Thiol/Disulfide Homeostasis and Oxidative/Nitrosative Stress in Patients with Crohn’s Disease - Aysun Bağdaş, Ancel; Barutçu, Sezgin; Saracaloğlu, Ahmet; Demiryürek, Abdullah Tuncay (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Crohn’s disease (CD) is a major subtype of chronic relapsing inflammatory gastrointestinal disorders. In this study, we assessed the possible contributions of serum oxidative/nitrosative stress and dynamic thiol/disulfide homeostasis to CD pathogenesis. Materials and Methods: Patients with active CD (A-CD) at onset (n = 38), CD patients in the remission (R-CD) (n = 38), and healthy controls (n = 38) were prospectively included in this study. Serum oxidative/nitrosative parameters as well as total thiol and native thiol levels were analyzed. Results: We observed significant augmentation in nitric oxide (NO) levels in both A-CD and R-CD patients compared to healthy controls. We detected marked reductions in the 3-nitrotyrosine levels in the patient groups. Glutathione, glutathione peroxidase, and myeloperoxidase levels were observed to be significantly lower in both the active and remission groups (P < .001). In the A-CD group, native thiol (P < .001) and total thiol (P < .01) levels were lower, and disulfide levels were higher than those of the control group (P < .01), while the native thiol/total thiol ratio was reduced and disulfide/total thiol (P < .001) and disulfide/native thiol (P < .001) ratios were elevated. Remarkably, no change in dynamic thiol/disulfide homeostasis was found in the R-CD group. Conclusion: Our results showed increased serum NO levels and decreased antioxidant enzymes, particularly during the active phase of CD. Determination of thiol/disulfide homeostasis could help differentiate between the active and remission phases of the disease. Thiol/ disulfide parameters can be used as biomarkers for A-CD. Cite this article as: Aysun Bağdaş A, Barutçu S, Saracaloğlu A, Demiryürek AT. Assessment of serum dynamic thiol/disulfide homeostasis and oxidative/nitrosative stress in patients with Crohn’s disease. Turk J Gastroenterol. 2025;36(2):114-123.